Estimation of Some Biomarkers in Recovered COVID19 Patients - Abeer Ghazi Nazzal; Ahmed Ghazi Sabbar (Journal of Techniques)
A novel pandemic COVID-19 occurred in 2019. Most studies across the world are concerned with this outbreak. In this prospective study, a certain biomarker was estimated as a predicting factor in 150 recovered COVID-19 patients and group of 50 healthy controls. The serum creatinine, Aspartate aminotransferase, Interlukin-24, prothrombin time, and fibrinogen were measured using different techniques. The results revealed that the level of AST in recovered patients exceeded that of the healthy control group with a highly significant difference. There was also a highly significant increase in the level of IL-24 in recovered patients in comparison with that in healthy control, while both prothrombin time and fibrinogen levels were lower in recovered patients compared to healthy control. We conclude that the variation in the level of parameters of interest may reflect a prognostic view in recovered COVID-19 patients.